The Association Between Nurses’ Caring Behaviors with Patient Satisfaction and Loyalty at Panti Waluya Hospital - Regina Hege; Kuswantoro Rusca Putra; Rinik Eko Kapti (Universitas Tribhuwana Tunggadewi, 2026)
Patient satisfaction and loyalty are important indicators of healthcare quality and hospital sustainability, and may be influenced by patients' perceptions of nurses' caring behaviors. This study aimed to analyze the association between nurses’ caring behaviors and patient satisfaction and loyalty at Panti Waluya Sawahan Hospital, Malang, Indonesia. A correlational study with a cross-sectional design was conducted involving 202 inpatients from July to September 2025. Eligible participants were patients aged ?18 years, hospitalized for at least three days, fully conscious, and able to communicate effectively. Participants were selected using proportional quota sampling across inpatient wards. Data were collected using the Caring Assessment Tool Version V (CAT V-27), the Public Service Satisfaction Questionnaire based on PERMENPAN-RB No. 14/2017, and a patient loyalty questionnaire adapted from Meesala and Paul (2018). Data were analyzed using Spearman's rho. Significant positive associations were found between nurses' caring behaviors and patient satisfaction (r? = 0.160; p = 0.023), nurses’ caring behaviors and patient loyalty (r? = 0.163; p = 0.020), patient satisfaction and patient loyalty (r? = 0.469; p 0.001). Nurses' caring behaviors were weakly associated with patient satisfaction and loyalty, whereas patient satisfaction showed a stronger association with patient loyalty. These findings highlight the importance of strengthening caring interactions as part of patient-centered nursing care while supporting continuous quality improvement to enhance healthcare experiences. Future studies should employ longitudinal or analytical designs to examine additional factors influencing patient satisfaction and loyalty.